2020
DOI: 10.1371/journal.ppat.1008495
|View full text |Cite
|
Sign up to set email alerts
|

Cofactor and glycosylation preferences for in vitro prion conversion are predominantly determined by strain conformation

Abstract: Prion diseases are caused by the misfolding of a host-encoded glycoprotein, PrP C , into a pathogenic conformer, PrP Sc. Infectious prions can exist as different strains, composed of unique conformations of PrP Sc that generate strain-specific biological traits, including distinctive patterns of PrP Sc accumulation throughout the brain. Prion strains from different animal species display different cofactor and PrP C glycoform preferences to propagate efficiently in vitro, but it is unknown whether these molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 70 publications
1
24
0
Order By: Relevance
“…All HEK-expressed constructs were partially deglycosylated using PNGase F as previously described ( S1 Fig ) to improve the conversion efficiency of Mo PrP C [ 28 ] ( S2 Fig ) . This effect is likely due to the previously observed inhibitory effects of PrPC glycosylation on the propagation of mouse prion strains[ 28 , 29 ], which may be due to negatively charged sialic acid groups within the glycan structure[ 30 ], and which may be further aggravated by hyper-glycosylation in HEK 293 cells. To ensure our system faithfully reproduces similar seed specificity as brain homogenate substrates in sPMCA, we first tested the susceptibility of cell-expressed BV PrP and Mo PrP in sPMCA ( Fig 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…All HEK-expressed constructs were partially deglycosylated using PNGase F as previously described ( S1 Fig ) to improve the conversion efficiency of Mo PrP C [ 28 ] ( S2 Fig ) . This effect is likely due to the previously observed inhibitory effects of PrPC glycosylation on the propagation of mouse prion strains[ 28 , 29 ], which may be due to negatively charged sialic acid groups within the glycan structure[ 30 ], and which may be further aggravated by hyper-glycosylation in HEK 293 cells. To ensure our system faithfully reproduces similar seed specificity as brain homogenate substrates in sPMCA, we first tested the susceptibility of cell-expressed BV PrP and Mo PrP in sPMCA ( Fig 2 ) .…”
Section: Resultsmentioning
confidence: 99%
“…Replication of transmissible, yet clinically silent PrP Sc states would not result in a clinical disease (76,77). Fourth, a spread of prions between brain regions is likely to be affected by region-specific differences in PrP C , such as differences in their sialylation status, and expression of strain-specific cofactors (59,78).…”
Section: Methodsmentioning
confidence: 99%
“…Another study, using desialylated PrP C , led to a proposal that PrP Sc amplification is increased because of the removal of electrostatic repulsion between N-glycans [ 68 ]. Although prion conversion is possible without glycans, the importance of investigating glycosylation in strains has been emphasized in a recent study, in which it was shown that strain conformation determines both cofactor and glycosylation preferences, supporting the strain-specific neurotropism hypothesis [ 69 ]. The same group of researchers has also shown in vitro that the second glycosylation site affects prion conversion, suggesting this site has a role in controlling the conversion of PrP Sc to PrP C [ 70 ].…”
Section: Discussionmentioning
confidence: 99%